1999
DOI: 10.1097/00005072-199902000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytoma Adhesion to Extracellular Matrix: Functional Significance of Integrin and Focal Adhesion Kinase Expression

Abstract: Evidence is accumulating implicating a role for integrins in the pathogenesis of cancer, a disease in which alterations in cellular growth, differentiation, and adhesive characteristics are defining features. In the present report we studied a panel of 8 human astrocytoma cell lines for their expression of integrin subunits by RT-PCR, and of integrin heterodimers by immunoprecipitation analyses. The functionality of integrin heterodimers was assessed using cell attachment assays to plastic or single matrix sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…Our data show that RNAi-mediated knockdown of p300 significantly increases the migration and invasion of U251 cells in vitro. This finding is consistent with the earlier observations by Rutka et al, who have demonstrated that elimination of GFAP in U251 cells with anti-sense RNA results in the marked decrease in cell adhesion and increase in invasiveness [12], which is associated with increased expression of β1 integrin [62] and CD44, and with redistribution of actin forming actin stress fibers implicated in the regulation of cell motility [63].…”
Section: Discussionsupporting
confidence: 93%
“…Our data show that RNAi-mediated knockdown of p300 significantly increases the migration and invasion of U251 cells in vitro. This finding is consistent with the earlier observations by Rutka et al, who have demonstrated that elimination of GFAP in U251 cells with anti-sense RNA results in the marked decrease in cell adhesion and increase in invasiveness [12], which is associated with increased expression of β1 integrin [62] and CD44, and with redistribution of actin forming actin stress fibers implicated in the regulation of cell motility [63].…”
Section: Discussionsupporting
confidence: 93%
“…17). Cells were transfected with MARCKS siRNA, control siRNA, or mock transfected for 72 h and then replated onto the coated 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Strikingly, CD44 and RHAMM are both suppressed by p53 (Godar et al 2008;Sohr and Engeland 2008), suggesting that early cellular progression through canonical checkpoints and the ability to migrate/invade are linked, although this possibility remains to be validated in glioma models. Integrins, particularly the avb3 and avb5 heterodimers (Bello et al 2001a), also likely contribute to glioma cell adherence to the ECM in a process that activates cytoskeletal rearrangement through cytoplasmic mediators, including FAK (Rutka et al 1999;Riemenschneider et al 2005) and/or Pyk2 (Lipinski et al 2008). Their putative involvement in glioma pathobiology (D'Abaco and Kaye 2007; Desgrosellier and Cheresh 2010) has prompted the testing of the avb3 and avb5 integrin inhibitor cilengitide in an ongoing phase III CENTRIC clinical trial for newly diagnosed glioblastoma in combination with radiation therapy and temozolomide (Reardon et al 2011a).…”
Section: Glioma Cell Invasionmentioning
confidence: 99%